Form CO2-responsive microemulsion for extracting ethanol from water by triethylamine. Issue 5 (May 2021) - Du, Wenting; Lyu, Ling; Zhang, Xin; Xu, Hongwei
Abstract: Compared with traditional distillation separation, extraction of ethanol from ethanol water could reduce the energy consumption. But emulsion generated in the process of strong mixing caused difficulty of separation of two phases. A new method of extraction ethanol could realize the efficient mass transfer and the complete separation of two phases. The microemulsion system was constructed by adding TEA (triethylamine) into ethanol water, and then ethanol was extracted from the water by 2-ethyl-1-hexanol. The extraction efficiency was close to the theoretical value, and the extracted emulsion could be demulsified under the action of CO2 . The method did not require strong stirring, and had low energy consumption and high extraction efficiency. It solved the problem to separate the emulsion generated in the process of ethanol extraction.